Comparison of Single Layer and Bilayer Biosensors Based on Crosslinking of Penicillinase for Potentiometric Detection of Penicillin in Milk and Antibiotics. Issue 6 (25th March 2015) - Ismail, Fatima; Adeloju, Samuel B.
Abstract The use of bilayers for fabrication of biosensors is advantageous for increasing enzyme loading. Substantial improvement in sensitivity is often achieved through immobilisation of the enzyme in both layers. In particular, the use of cross linking agents such as glutaraldehyde (GLA), bovine serum albumin (BSA) and polyvinyl alcohol (PVA) are beneficial for enhancing enzyme stability and, hence, for fabricating stable biosensors. The successful fabrication of a single layer BSA‐GLA‐P'nase biosensor for potentiometric detection of penicillin is described. Subsequently, the three crosslinking agents were employed with two polymers, polypyrrole (PPy) and polytyramine (PTy), together with penicillinase (P'nase) for fabrication of PPy‐NO3‐P'nase/BSA‐PVA‐P'nase and PTy‐NO3‐P'nase/BSA‐GLA‐P'nase bilayer biosensors. The analytical performances of the bilayer biosensors were then compared with the single layer BSA‐GLA‐P'nase biosensor for the determination of penicillin in milk and amoxycillin tablets. While the determination of penicillin in milk was somewhat problematic, its determination in amoxicillin tablets proved to be successful, with recoveries of 102±15 % obtained with the PPy‐NO3‐P'nase/BSA‐PVA‐P'nase biosensor, 100±19 % with PTy‐NO3‐P'nase/BSA‐GLA‐P'nase biosensor and 103±5 % with BSA‐GLA‐P'nase biosensor. Notably, the results of the latter agreed favourably with those obtained through a reference titrimetric method.